SIFAT FISIK TANAH DI BAWAH TEGAKAN EBONI ( Diospyros celebica Bakh ) PADA KAWASAN CAGAR ALAM PANGI BINANGGA KABUPATEN PARIGI MOUTONG - Evarnaz, Novita; Toknok, Bau; Ramlah, Sitti (Universitas Tadulako, 2014)
The function of soil is a medium for growth and root development in supporting plants to grow and supply the need of water and nutrients to the planst roots. The issue raised in this study is how the physical properties of soil, including the texture, structure, porosity, bulk density and permeability of soil under the stand of ebony at the Natural Reserve of Pangi Binangga. Ebony is one of the endemic tree species in Sulawesi Island including Central Sulawesi. The purpose of this study was to determine the physical properties of soil under the stands of ebony at the Natural Reserve of Pangi Binangga, Parigi Moutong Regency. This study was conducted for 3 months (May-July 2013) at the Natural Reserve of Panggi Binangga, Sakina Jaya Village, Parigi Moutong Regency, Central Sulawesi Province. This study used survey and analysis in the laboratory. Soil samples were collected by using purposive sampling technique, that is, deliberately having particular consideration: the level of slope 0-8%, 8-15%, 15-25%, and 25-40%. The number of soil samples was 16 soil samples taken from the four slopes in two depths (0-30 cm and 30-60 cm). The study shows that the soil under the stands of ebony has a sandy loam soil texture class and loamy sand, structure soil crusts and granular, slight porous and porous (37.84 to 58.07%), rapid and very fast permeability (13,27 to 36,10 cm/h) and has a high and very high of bulk density of the medium (1.11 to 1.65 g/cm3). Keywords: Diospyros celebica, natural reserve, Pangi Binangga, soil physical property